Effects of Concept Mapping Instructional Strategy on Students’ Academic Achievement in Building Drawing in Technical Colleges in Rivers State - Ibeneme, O. T.; Ogubio, H. R. (Journal of Research in Industrial Technology and Educational Studies, 2026)
This study investigated the effect of concept mapping instructional strategy on students’ academic achievement in building drawing in technical colleges in Rivers State. Specifically, this work sought to determine the effect of concept mapping instructional strategy on academic achievement mean scores of students in building drawing and the effect of concept mapping instructional strategy on academic achievement mean scores of male students in building drawing. A quasi-experimental design guided the study. The population for this study consisted of 228 (202 male and 26 female) level II building technology students offering building drawing in the five technical colleges in Rivers State. Multistage sampling was used in selecting 104 level II building technology students for the study. Two objectives, research questions and hypotheses were formulated, answered and tested at .05 level of significance. The instrument for data collection was Basic Design Process Achievement Test developed by the researcher. The instruments were subjected to face and content validity by three experts from Nnamdi Azikiwe University Awka. The reliability of the instruments was established using Kuder Richardson Formula 20. The coefficient of the reliability obtained for equivalent test was .86. Mean and Standard Deviation were used to answer the research questions while z-test statistical tool was used to test the hypotheses. The findings of this study showed that experimental group taught with concept mapping performed better than the control group taught with conventional method. Furthermore, it was concluded that there was a significant difference between the effect of concept mapping instructional strategy on academic achievement mean scores of students in building drawing when compared with students taught using conventional instructional strategy. Therefore, it was recommended among others that concept mapping instructional strategy should be included in the National Teachers Certificate curriculum for teaching building drawing so that teachers can adopt its use for effective teaching.
Keywords: Academic achievement; Building drawing; Concept mapping; Instructional strategy; Technical College